Students’ educational game acceptance in higher education in Saudi Arabia - Aljuaid, Nada Mansour (Roman Science Publications, 2022)
Studies on educational games (EG) have shown growing interest among researchers due to the potential and preferences of the younger generation. Games technology is among the most popular forms of technology nowadays with billions of transactions yearly. Compared to traditional learning, games have features to provide opportunities for more enjoyable and engaging learning. Despite their great potentials, studies done among researchers on educational-game acceptance among students and teachers are still limited. This is due to challenges to design EG that is well-balanced between fun and learning features. Therefore, it is important to explore factors that contribute to the acceptance of EG. Despite many studies done on EG acceptance, most have only focused on the acceptance factors but not on the game features themselves. Thus, this study fills the gap by integrating the game-design factors, namely feedback, challenges, goals, and rewards, into the Extended Technology Acceptance Model (TAM) that contains 10 constructs and 66 items. A quantitative study among 300 survey participants has been administered at Taif University in Saudi Arabia. Data have been analysed using the structural equation modeling by utilising the PLS-SEM tool. Findings show that game-design features, which are challenges, goals, and rewards, are significant on perceived ease of use, while feedback and challenges are significant on perceived usefulness. Features, goals, challenges, and rewards have a significant effect on perceived usefulness, while intention to use educational games is influenced by learning content, enjoyment, and perceived usefulness. In conclusion, several game-design features are important to be incorporated into EG to ensure the presence of its fun elements while not compromising the learning features. Therefore, educational-game designers and developers should integrate these factors in game design and development in order to increase student engagement and acceptance of educational games.